Improved microphysical parametrization of drizzle and fog for operational forecasting using the Met Office Unified Model. (13th June 2012) - Wilkinson, Jonathan M.; Porson, Aurore N. F.; Bornemann, F. Jorge; Weeks, Mark; Field, Paul R.; Lock, Adrian P.
Abstract: In order to improve the forecasting of fog, visibility and drizzle within the Met Office Unified Model, three parametrizations are included in high‐resolution, limited‐area versions of the model. These are (i) improved rainfall speeds; (ii) linking aerosol to the autoconversion scheme; and (iii) a taper curve for cloud droplets near the surface. The results show a better representation of low‐visibility conditions in winter. There is a general reduction in drizzle and a better representation of drizzle depending on whether the air mass is clean or polluted. Summertime occurrences of fog are also reduced and are now under‐forecast, which will require a further investigation to correct. The package described in the paper has been made operational in the 4 and 1.5 km operational forecast versions of the Unified Model during the spring and summer of 2011, showing an improvement in model performance and a reduction in model error. This demonstrates the ability to improve operational NWP forecasts by coupling cloud and aerosol processes. Copyright © 2012 British Crown copyright, the Met Office. Published by John Wiley & Sons Ltd.